Child art and cat’s cradle: investigating play and games in Britten’s ‘The Turn of the Screw’ (1954) - Leccia, M (2023)
Lover of sporting, driving fast cars, having gobbledygook conversations with children, reading children books and poetry, writing music accessible for children as well as adults, and composing music for children to perform, Benjamin Britten displayed all along his life a constant playful attitude. This attitude can be analysed in his aesthetic, at the boundary of violence and play, and in his compositional processes. Moreover, this playful aesthetic finds its sources in the French and Victorian child phantasmagoria, Stravinskyian puppet-like musical motives, or Picasso’s inspiration from child art. This presentation focuses on two passages of ‘The Turn of the Screw’ (1954), where Benjamin Britten and Myfanwy Piper’s playful art meets the playful manipulative techniques of Henry James. Through child art, musical/literal games, and sport-like gestures, this renewed analysis of the opera will demonstrate how an apparent unseriousness participate to a deepened violence.